Approach to Inversion Design of Dielectric Material Based on the First‐Principle. Issue 1 (1st January 2017) - Miao, Qiang; Wu, Dewei; He, Jing; Yang, Chunyan; Xie, Lei
Abstract : The first‐principle is an effective method for the material property calculation. One inversion design idea of dielectric material based on the first‐principle was put forward. In this kind of material design thought, the specific demanded dielectric property of material is the starting point of the whole design course. The atomic structure characteristic of the material is solved using the inversion model based on the first‐principle. And the key issues needing researching were discussed, these problems were quantized structure of electromagnetic and optic field, the quantized polarization theory of dielectric material, the uniform calculation method of dielectric property and the dielectric material inversion model.